Penurunan Parameter Pencemar Limbah Cair Industri Tekstil Secara Koagulasi Flokulasi (Studi Kasus: IPAL Kampung Batik Laweyan, Surakarta, Jawa Tengah, Indonesia) - Elvis Umbu Lolo; Yonathan Suryo Pambudi (Jurnal Serambi Engineering, 2020)
The batik home industry of Kampung Laweyan, Surakarta City did not make efforts to prevent environmental pollution from the wastewater produced. Waste water is discharged into the Jenes river, so that the river becomes polluted and contributes to the pollution of the Bengawan Solo River Basin. The study was conducted at the Environmental Laboratory, Environmental Engineering Study Program, Faculty of Engineering, Surakarta Christian University by conducting the coagulation process of flocculation with the jart test. This study uses variations and dosages of the type of FeSO4 and PAC coagulants with levels of 5% each for 100 ml / sec waste discharge. The results of the research are that before the waste is processed by the coagulation process, the value of BOD = 660.28 mg / l and COD = 1600. After the coagulation process, the efficiency of each type of coagulant is with FeSO4, BOD = 85.63% and COD = 82.67 %. With PAC coagulant, BOD = 90.21%, COD = 88.97%. This shows that the ability of PAC to reduce pollutant parameters is greater than ferrous sulfate.